Back to the Shop Floor: Behavioural Insights from Workplace Sociology. (December 2019) - Pendleton, Andrew; Lupton, Ben; Rowe, Andrew; Whittle, Richard
This article compares insights into decision-making and behaviour developed by Kahneman and Tversky in behavioural economics with the main findings from studies of pay incentives in workplace sociology in the middle decades of the 20th century. The article shows how many of the insights offered by behavioural economists, such as loss aversion, were anticipated and considered by the workplace sociologists. It is argued that the sociological studies offer deeper and more convincing accounts of worker behaviour through a better understanding of the role of social structure, context, and social processes in framing and influencing action.